Forensic classification of narcotic drugs - R. L. Stepaniuk; S. M. Lozova (Bulletin of Kharkiv National University of Internal Affairs)
The development of means and methods for preventing and combating drug-related crime depends on an understanding of trends in the illicit drug market. This requires the use of a forensic classification of the relevant substances. Currently, there are significant gaps in this issue due to the use of different approaches to its construction, which causes difficulties in conducting scientific research and in practical activities aimed at solving and investigating criminal offences.